The Effectiveness of the In-Service Training Model towards Improving Madrasah Ibtidaiyah Teachers' Performance in Supporting National Assessment Policy - Moh Masnun; Patimah Patimah; Tati Nurhayati; Ardian Maulana; Ziah Pandani (Al Ibtida: Jurnal Pendidikan Guru MI, 2024)
AbstractThis study aims to investigates the effectiveness of the In-Service Training model in enhancing the performance of Madrasah Ibtidaiyah teachers in Indonesia, particularly in alignment with the National Assessment Policy. This research is a qualitative research using observation, interviews, and documentation for data collection. We analyzed the data through reduction, presentation, and conclusion stages. Findings indicate that the in-service training model significantly benefits Madrasah Ibtidaiyah teachers to improve their ability to support educational policy goals. Teachers and school leaders expressed a desire for sustained, needs-based training. Factors that facilitate successful training implementation include active participation by all teachers and school principals, positive attitudes toward professional development, and alignment of training activities with school-specific needs. However, there are persistent challenges, such as limited school resources, inadequate internet access, and teachers' low proficiency in digital skills. Furthermore, training availability often depends on external funding, such as school operational assistance affirmation grants, underscoring budget constraints as a barrier to consistent professional growth.Keywords: in-service training model, madrasah ibtidaiyah teachers performance, national assessment.Â AbstrakPenelitian ini bertujuan untuk menyelidiki efektivitas model Pelatihan Dalam Jabatan (in-service training) dalam meningkatkan kinerja guru Madrasah Ibtidaiyah di Indonesia, khususnya yang selaras dengan Kebijakan Penilaian Nasional. Penelitian ini merupakan penelitian kualitatif dengan menggunakan observasi, wawancara, dan dokumentasi untuk pengumpulan data. Data dianalisis melalui tahap reduksi, penyajian, dan kesimpulan. Temuan penelitian ini menunjukkan bahwa model In-Service Training secara signifikan memberikan manfaat bagi guru madrasah ibtidaiyah dalam meningkatkan kemampuan mereka untuk mendukung tujuan kebijakan pendidikan. Guru dan pimpinan sekolah menyatakan keinginan mereka untuk mendapatkan pelatihan yang berkelanjutan dan berbasis kebutuhan. Faktor-faktor yang memfasilitasi keberhasilan pelaksanaan pelatihan diantaranya partisipasi aktif dari semua guru dan kepala sekolah, sikap positif terhadap pengembangan profesional, dan penyelarasan kegiatan pelatihan dengan kebutuhan sekolah. Namun, tantangan tetap ada, terutama sumber daya sekolah yang terbatas, termasuk akses internet yang tidak memadai dan rendahnya kemampuan guru dalam keterampilan digital. Selain itu, ketersediaan pelatihan sering kali bergantung pada pendanaan eksternal, seperti dana BOS Afirmasi, yang menggarisbawahi keterbatasan anggaran sebagai penghalang bagi pertumbuhan profesional yang konsisten.Kata kunci: model in-service training, kinerja guru madrasah ibtidaiyah, asesmen nasional.